Cancer patients' satisfaction with communication and information given by nurses at teaching hospitals of Tehran, Iran. - Akhtari Zavare, Mehrnoosh; Abdullah, Mohd Yunus; Syed Hassan, Syed Tajuddin; Md Said, Salmiah; Mohammad Kamali, (Tehran University of Medical Sciences, 2011)
Background: Effective patient–professional communication can be of crucial importance to long-term psycho-social outcomes in patients with cancer. A cross sectional study was conducted to examine cancer patients' satisfaction with regard to various aspects of communication and information given by nurses. Methods: A proportional stratified sampling method was done and data collected via face-to-face interview based on a validated Patient Satisfaction Questionnaire (PSQ) during a 3 month period. A total of 384 patients aged 14 years old and above were selected. Results: The majority of respondents were males (52.3%) and married (66.4%), working (52.6%) and age group 45-54 year (26.6%) with secondary education level (44.8%), and 53.1% of them admitted at teaching hospitals of government A University of Medical Science. The findings revealed that a vast majority of respondents (81.5%) were satisfied with communication and information given by nurses, while the others (18.5%) not. There was significant relationship between patients’ satisfaction and age group (p ≤ 0.05). Also, the age groups of 15-44 years old and married patients were the best predictors for level of cancer patients’ satisfaction with communication, and information given by nurses. Conclusion: Key findings are a number of issues with regard to information and communication which can be clearly improved within teaching hospitals of in Tehran city. The study concluded that patient– professional communication should be tailored to meet individual need.